2015
DOI: 10.1007/s11104-015-2672-5
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic colonization of Arabidopsis thaliana by Gluconacetobacter diazotrophicus and its effect on plant growth promotion, plant physiology, and activation of plant defense

Abstract: Background and aims Gluconacetobacter diazotrophicus is a plant growth-promoting bacteria (PGPB) that colonizes several plant species. Here, we studied the internal colonization of Arabidopsis thaliana tissues by G. diazotrophicus and analyzed its effects on physiology, growth, and activation of plant immune system during such association.Methods A. thaliana seedlings were inoculated with G. diazotrophicus and grown in substrate for 50 days. Effects on plant growth were estimated by quantifying number of leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 88 publications
(106 reference statements)
0
30
0
Order By: Relevance
“…The dotted line indicates when the yield of the full recommended rate of N fertilizer* according to the total available N in the soil pre-sowing is equivalent to the yield of the NFix ® treatment only research that has been conducted in this field with Gd has involved the inoculation of Arabidopsis thaliana. In this study, Gd had beneficial effects on photosynthesis [90]. Whole-canopy photosynthesis levels were 68% higher in inoculated plants compared to uninoculated plants.…”
Section: Agricultural Value Of G Diazotrophicusmentioning
confidence: 53%
See 1 more Smart Citation
“…The dotted line indicates when the yield of the full recommended rate of N fertilizer* according to the total available N in the soil pre-sowing is equivalent to the yield of the NFix ® treatment only research that has been conducted in this field with Gd has involved the inoculation of Arabidopsis thaliana. In this study, Gd had beneficial effects on photosynthesis [90]. Whole-canopy photosynthesis levels were 68% higher in inoculated plants compared to uninoculated plants.…”
Section: Agricultural Value Of G Diazotrophicusmentioning
confidence: 53%
“…As a consequence of greater carbon uptake and lower water loss through transpiration, inoculated plants showed increases of 94.5% in whole-canopy water-use efficiency compared to non-inoculated plants. These results suggest that Gd positively affects plant physiology by increasing the photosynthetic capacity and improving water-use efficiency [90], which goes some way to explaining the parallel yield relationships across all levels of N fertilizers, shown in Figs. 1 and 2.…”
Section: Agricultural Value Of G Diazotrophicusmentioning
confidence: 68%
“…These techniques include chlorophyll levels and leaf percentage nitrogen [17], nitrogenase activity measured through an acetylene reduction assay (ARA) [136,137], nif gene mutant studies [138], labeled nitrogen 15 N2 studies [137][138], enhanced photosynthetic rates [16] and plant growth and yield benefits [12,19,139,140].…”
Section: Nitrogen Fixation In G Diazotrophicusmentioning
confidence: 99%
“…It has been demonstrated that strains of G. diazotrophicus differentially affected growth parameters of sugarcane, with some strains improving germination, tiller number and plant height relative to others [14] and there is also evidence that G. diazotrophicus improves tolerance to the sugarcane pathogen Xanthomonas albilineans as a result of production of bacteriocin; as well as reducing galling caused by root knot nematodes (Meloidogyne incognita) in bottle gourds and cotton [15]. G. diazotrophicus has also been shown to enhance photosynthetic capability and water use efficiency [16] and in sorghum increased chlorophyll and leaf nitrogen [17].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most sugar-tolerant bacteria reported is Gluconacetobacter diazotrophicus, which can tolerate water activity as low as 0.892 when cultured under high sugar concentrations . G. diazotrophicus is an endophytic plant growth-promoting bacteria (PGPB) that was first isolated from sugarcane (Cavalcante and Dobereiner, 1988) and is able to promote plant growth when inoculated in several species (Vargas et al, 2014;Rangel de Souza et al, 2015;Sahai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%